New options on the horizon for nononcogene addicted non-small-cell lung cancer. (10th July 2018) - Paglialunga, Luca; Ricciardi, Serena; D'Arcangelo, Manolo
The treatment of non-small-cell lung cancer (NSCLC) has historically been based on platinum doublets- and taxan-based chemotherapy in the first- and second-line therapy, respectively. Although new agents have emerged for patients with driver mutations, treatment options for nononcogene addicted NSCLC have not changed for years. However, the last 5 years have seen the approval and introduction of new biological agents, such as immune checkpoint inhibitors and antiangiogenic drugs. The aim of this review is to give readers an update on the news in the treatment of nononcogene addicted NSCLC. As more and more therapeutic options are now available, we will delineate a potential therapeutic algorithm for the optimization of daily life treatment choice of NSCLC patients.